In situ Response of Tropical Coralline Algae to a Novel Thermal Regime - Bach, Lydia L.; Freer, Jennifer J.; Kamenos, Nicholas A. (Frontiers in Marine Science, 2017)
Coralline algae provide important ecosystem services. In situ observations of how they respond to different environmental conditions can help us to understand i) their ability to adapt to their local environment and ii) their capacity to acclimatize to a novel thermal regime. Here, individuals of the tropical coralline algae, Lithophyllum kotschyanum, were translocated on a coral reef from thermally stable areas to areas characterised by natural temperature variability. Changes in their photosynthetic efficiency were determined using pulse amplitude modulation (PAM) chlorophyll fluorescence. Despite an initial stress response, algae exposed to increases in thermal variation recovered within 24h, indicating a rapid, short-term acclimatisation capacity. Algae naturally inhabiting thermally variable areas of the reef showed no change in photosynthetic efficiency throughout the study suggesting longer-term adaptation to living in a variable environment also occurs. However, analysis indicated that coralline algae living in thermally stable reef areas were abundant and marginally larger, suggesting physiological trade-offs are used to survive in variable environments. Thus, our results suggest that while coralline algae can survive in environmentally variable conditions, there may be structural and ecosystem costs.